Method for preparing 1,4-cyclohexane dicarboxylic acid by hydrogenation of terephthalic acid with hollow nitrogen-doped carbon spheres loaded bimetallic nickel-cobalt catalyst

CN122937841APending Publication Date: 2026-10-20TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611293566.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

贵金属路线以Ru、Pd为核心活性组分,彭宇轩等人在《应用化学》期刊公开Ru/CeO2催化剂用于PTA直接加氢,虽可提升底物转化效率,但酸性水环境下Ru活性组分易酸蚀、高温团聚,且PTA脱羧生成CO、CO2会吸附毒化活性中心,多次循环后活性明显衰减;李筱玲等人于《石油化工》刊发Ru/C催化PTA加氢的相关研究,该体系虽可实现较高PTA转化率,但催化剂无法区分苯环与羧基吸附位点,羧基氢解副反应严重,产物组分复杂,且贵金属储量稀缺、原料成本持续高位,仅依靠载体改性、少量助剂掺杂仅能小幅优化性能,无法从根源平衡成本与长效稳定性

Benefits of technology

[0043]第四,外层连续致密的氮掺杂碳壳层作为物理屏障,将内部金属纳米颗粒与液相酸性反应体系物理隔离,阻断了H⁺向金属表面的直接迁移路径,抑制了活性金属的酸蚀溶出;同时,碳壳层的微孔结构允许H2分子和有机底物分子自由进出,使加氢反应得以正常进行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a method for the hydrogenation of terephthalic acid to 1,4-cyclohexanedicarboxylic acid using a hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst. The catalyst has a hollow spherical core-shell microstructure with an internal hollow cavity and an external continuous nitrogen-doped carbon shell. Nickel-cobalt bimetallic nanoparticles are uniformly embedded in the inner wall and surface of the carbon shell. Using the hollow nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst as the hydrogenation active component, terephthalic acid, the catalyst, and a solvent are added to a high-pressure reactor. After hydrogen purging, the reactor is pressurized to 1-6 MPa and stirred at 100-200°C for 1-10 h. The reaction product is then subjected to solid-liquid separation, washing, and drying to obtain 1,4-cyclohexanedicarboxylic acid. This invention uses a non-precious metal bimetallic catalyst instead of a precious metal catalyst. This preparation method is simple, environmentally friendly, and exhibits excellent catalyst stability. The conversion rate of terephthalic acid can reach over 99%, and the selectivity of 1,4-cyclohexanedicarboxylic acid can reach over 98%. The production cost is low, and it has good prospects for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic hydrogenation and fine chemical technology, specifically relating to a method for the hydrogenation of terephthalic acid to 1,4-cyclohexanedicarboxylic acid using a hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst. Background Technology

[0002] Catalytic hydrogenation of terephthalic acid (PTA) and its ester derivatives is a crucial technological pathway for preparing high-end polymer monomers such as 1,4-cyclohexanedicarboxylic acid (CHDA). Due to its molecular structure, both the benzene ring and carboxyl group within the PTA molecule possess hydrogenation activity, and the hydrogenation reactions of these two groups are in significant competition. Simultaneously, the polar carboxyl group readily adsorbs strongly onto the surface of metal catalytic active sites, inhibiting the benzene ring hydrogenation process. This makes it difficult to precisely control the product selectivity of the directional saturated hydrogenation of the PTA benzene ring to prepare CHDA, which is a core technological barrier hindering the industrialization of this process.

[0003] Currently, the mainstream catalytic systems in the industry are divided into three categories: precious metal catalytic systems, precious metal-nickel composite bimetallic systems, and pure nickel-based non-precious metal systems. The precious metal route uses Ru and Pd as the core active components. Peng Yuxuan et al. published a Ru / CeO2 catalyst for direct PTA hydrogenation in the journal *Applied Chemistry*. Although it can improve substrate conversion efficiency, the Ru active component is prone to acid corrosion and high-temperature aggregation in acidic water environments. Furthermore, the CO and CO2 generated from PTA decarboxylation adsorb and poison the active sites, leading to significant activity decay after multiple cycles. Li Xiaoling et al. published a study on Ru / C catalytic PTA hydrogenation in *Petrochemical Technology*. While this system can achieve a high PTA conversion rate, the catalyst cannot distinguish between benzene ring and carboxyl group adsorption sites, resulting in severe carboxyl group hydrogenolysis side reactions, complex product composition, and the scarcity of precious metal reserves and persistently high raw material costs. Relying solely on support modification and a small amount of additive doping can only slightly optimize performance and cannot fundamentally balance cost and long-term stability.

[0004] To reduce the cost of using precious metals, Beijing University of Chemical Technology developed a supported ruthenium-nickel bimetallic catalyst for the hydrogenation of PTA to CHDA. Under suitable temperature and pressure conditions, it can achieve a substrate conversion rate of approximately 99%. However, this system still relies on the precious metal ruthenium. Conventional alumina and hydrotalcite supports lack a sealed protective layer, and in the acidic reaction system, hydrogen ions continuously corrode the active metal sites, resulting in significant metal leaching losses. After multiple cycles, the catalytic activity irreversibly decreases, and the CHDA selectivity is only 95%. Conventional supported nickel-based catalysts that do not use precious metals have even more pronounced shortcomings. Existing literature reports that under optimal conditions, the PTA conversion rate is only 90.1%, and the CHDA selectivity is less than 85%, with numerous byproducts and high separation and purification loads.

[0005] Existing research has optimized the physicochemical properties and catalytic performance of nickel-based catalysts through strategies such as support confinement, nitrogen doping modification, and bimetallic synergy. However, under the acidic high-pressure conditions of PTA benzene ring-directed hydrogenation, there is still a lack of effective solutions for how to synergistically balance catalytic activity, target product selectivity, and long-term operational stability of the catalyst.

[0006] In summary, developing a metal-free, mild reaction process for the directional hydrogenation of terephthalic acid that can simultaneously achieve high catalytic activity and benzene ring hydrogenation specificity, and solving common technical problems in the industry such as easy poisoning of active sites, high catalytic costs, and difficulty in catalyst control, is a key research focus that urgently needs to be addressed in this field. Summary of the Invention

[0007] Existing conventional nickel-based catalysts used for the hydrogenation of the aromatic ring of terephthalic acid exhibit weak interfacial interactions between the metal and the support. At high temperatures, the active metal particles are prone to agglomeration and sintering. Simultaneously, the catalyst lacks a protective structure, leading to significant dissolution and loss of the active metal in acidic aqueous reaction systems. Both factors contribute to extremely poor catalyst cycle stability. In actual continuous industrial production, metal particle agglomeration and sintering significantly reduce effective hydrogenation sites, resulting in a continuously decreasing PTA conversion rate per reaction, increased raw material consumption, and exacerbated side reactions such as carboxyl hydrogenolysis and partial hydrogenation of the benzene ring. This increases the product distillation and separation load and waste treatment costs. Furthermore, the large-scale dissolution of the active metal component not only accelerates catalyst deactivation, forcing frequent shutdowns for catalyst replacement and reducing continuous production efficiency, but also increases the difficulty of wastewater treatment and additional environmental disposal costs due to the dissolved metal ions entering the mother liquor.

[0008] To address the aforementioned deficiencies in the prior art, the first objective is to provide a preparation process for the hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst. This process is simple, the metal component ratio is adjustable, and the catalyst exhibits a hollow spherical core-shell structure with an internal cavity and an external continuous nitrogen-doped carbon shell. Active metal nanoparticles are uniformly dispersed on the inner wall and surface of the carbon shell. The catalyst demonstrates good batch-to-batch reproducibility and possesses potential for large-scale industrial scale-up. The second objective of this invention is to provide a method for catalyzing the hydrogenation of terephthalic acid to 1,4-cyclohexanedicarboxylic acid using a hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst.

[0009] To achieve the above objectives, the present invention provides the following technical solution:

[0010] A hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst is developed. The catalyst has a hollow spherical core-shell microstructure with a hollow cavity inside and a continuous nitrogen-doped carbon shell on the outside. Nickel-cobalt bimetallic nanoparticles are uniformly embedded in the inner wall and surface of the carbon shell.

[0011] The preparation method of a hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst includes the following steps:

[0012] 1) Disperse the hard template in a solvent, add nickel salt, cobalt salt, carbon source and nitrogen source, stir for 1-4 h to obtain a mixed solution;

[0013] 2) The mixed solution is rotary evaporated under reduced pressure at 40-80°C until the solvent is completely evaporated to obtain the catalyst precursor;

[0014] 3) The obtained precursor is heated to 600-900°C at a heating rate of 1-10°C / min under a nitrogen or argon atmosphere and pyrolyzed at a constant temperature for 1-4 h to obtain the pyrolysis product;

[0015] 4) The obtained pyrolysis product was etched with alkaline solution to remove the hard template. After washing and drying, a hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst was obtained.

[0016] The method for preparing the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst, wherein the hard template is any one of solid SiO2 microspheres, mesoporous SiO2, or SiO2 aerogel.

[0017] The method for preparing the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst, wherein the nickel salt is any one of nickel nitrate, nickel chloride, or nickel acetate; and the cobalt salt is any one of cobalt nitrate, cobalt chloride, or cobalt acetate.

[0018] The method for preparing the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst, wherein the carbon source is any one of glucose, sucrose, furfuryl alcohol or phenolic resin; the nitrogen source is any one of dicyandiamide, melamine or urea; and the mass ratio of nitrogen source to carbon source is 1:1 to 1:10.

[0019] The method for preparing the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst, wherein the total mass ratio of the nickel salt and cobalt salt to the nitrogen source is 1:2 to 1:10; and the total mass ratio of the nickel salt and cobalt salt to the carbon source is 1:5 to 1:15.

[0020] The method for preparing the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst, wherein the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 1-4 mol / L.

[0021] The method for preparing 1,4-cyclohexanedicarboxylic acid by catalytic hydrogenation of terephthalic acid according to the present invention includes the following steps:

[0022] 1) Add the hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst, terephthalic acid, and solvent into a high-pressure reactor and seal the reactor;

[0023] 2) After replacing the air in the reactor with hydrogen, fill it with hydrogen to a pressure of 1.0–6.0 MPa, heat it to 100–200°C, and react it with stirring for 1–10 h;

[0024] 3) After the reaction is complete, allow the autoclave to cool naturally to room temperature, and then separate the solid and liquid phases to obtain 1,4-cyclohexanedicarboxylic acid.

[0025] The present invention relates to a method for preparing 1,4-cyclohexanedicarboxylic acid by catalytic hydrogenation of terephthalic acid, wherein the mass ratio of the catalyst to terephthalic acid is 1:1 to 1:10; and the concentration of terephthalic acid is 0.05 to 0.5 mmol / mL.

[0026] The present invention relates to a method for preparing 1,4-cyclohexanedicarboxylic acid by catalytic hydrogenation of terephthalic acid, wherein the solvent is one or more of water, methanol, ethanol, isopropanol, tetrahydrofuran, or 1,4-dioxane.

[0027] Under the above-mentioned preferred conditions, terephthalic acid can be efficiently and selectively converted into 1,4-cyclohexanedicarboxylic acid.

[0028] The specific explanation is as follows:

[0029] In the above preparation method, the use of hard templates ensures the formation of hollow structure in the catalyst; during high-temperature pyrolysis, carbon source carbonizes to form carbon shell, nitrogen source is doped into carbon skeleton, and nickel salt and cobalt salt are reduced in situ to metal nanoparticles and loaded onto carbon shell.

[0030] Furthermore, the hard template is any one of solid SiO2 microspheres, mesoporous SiO2, or SiO2 aerogel; preferably, the particle size of the solid SiO2 microspheres is 50–500 nm. The size of the hard template directly determines the cavity size of the hollow spherical structure in the catalyst.

[0031] Furthermore, the nickel salt is any one of nickel nitrate, nickel chloride, or nickel acetate; the cobalt salt is any one of cobalt nitrate, cobalt chloride, or cobalt acetate.

[0032] Furthermore, the carbon source is any one of glucose, sucrose, furfuryl alcohol, or phenolic resin; the nitrogen source is any one of dicyandiamide, melamine, or urea.

[0033] Preferably, the mass ratio of the nitrogen source to the carbon source is 1:1 to 1:10. An appropriate nitrogen source ratio is beneficial for increasing the doping amount of pyridine nitrogen and graphitic nitrogen in carbon materials and enhancing the metal-support interaction.

[0034] Preferably, the total mass ratio of the nickel salt and cobalt salt to the nitrogen source is 1:2 to 1:10.

[0035] Preferably, the total mass ratio of the nickel salt and cobalt salt to the carbon source is 1:5 to 1:15. Within this ratio range, the metal nanoparticles can be uniformly dispersed on the carbon shell surface, avoiding aggregation while ensuring a sufficient number of active sites.

[0036] More preferably, the heating rate is 3 to 8°C / min.

[0037] Furthermore, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 1–4 mol / L. Alkaline etching can gently and efficiently remove the hard template without damaging the overall structure of the carbon shell.

[0038] This invention employs a hard template method to construct a hollow spherical core-shell structure. Solid SiO2 microspheres are used as hard templates, and nickel salts, cobalt salts, carbon sources, and nitrogen source precursors are loaded onto their surfaces via an impregnation-drying method. After high-temperature pyrolysis, the carbon source carbonizes into a continuous carbon shell, the nitrogen source is doped into the carbon framework to form a nitrogen-doped carbon layer, and the nickel and cobalt salts are thermally reduced in situ to zero-valent metal nanoparticles, which are then embedded in the inner wall and surface of the carbon shell. Subsequent alkaline etching removes the SiO2 core, resulting in a hollow spherical core-shell structure with an internal hollow cavity, an external nitrogen-doped carbon shell, and metal nanoparticles loaded on the inner wall and surface of the carbon shell. The key features of this structure are: the size of the hollow cavity can be controlled by the particle size of the SiO2 microspheres; the thickness of the carbon shell can be adjusted by the amount of precursors used; and the particle size and loading of the metal nanoparticles can be controlled by the metal salt feed ratio. These three structural parameters are independently adjustable, providing a flexible structural design space for optimizing catalytic performance.

[0039] The hydrogenation performance of the catalyst of this invention originates from the synergistic effect of the hollow nitrogen-doped carbon shell, the bimetallic synergistic effect, and the protection of the closed carbon shell.

[0040] First, the hollow spherical core-shell structure endows the catalyst with a large specific surface area and ample internal space, which is conducive to the enrichment and diffusion of reactant molecules on the carbon shell surface. At the same time, the hollow cavity can accommodate product molecules and release them in a timely manner, avoiding excessive adsorption of products at the active sites. In addition, the physical confinement effect of the hollow structure on metal nanoparticles can effectively inhibit their migration and aggregation under high-temperature reaction conditions, thereby maintaining the long-term dispersion stability of the active components.

[0041] Second, after nitrogen doping is incorporated into the carbon framework, the nitrogen-containing functional groups (pyridine nitrogen, graphitic nitrogen, etc.) on the carbon shell surface can act as anchoring sites to form Ni(N)-Co coordination bonds with metal nanoparticles. This enhances the metal-support interaction, promotes the transfer of electrons from the carbon support to the active metal center, modulates the electron cloud density of the metal, thereby optimizing the adsorption configuration of the benzene ring in the terephthalic acid molecule and lowering the activation energy barrier for aromatic ring hydrogenation. Simultaneously, nitrogen doping imparts a certain degree of basicity to the carbon shell, which can neutralize the chemical corrosion of the active metal by acidic substrates and products in the reaction system.

[0042] Third, the combination of nickel and cobalt bimetals can produce an alloy synergistic effect. Nickel provides the main hydrogen activation and hydrogenation activity, while the introduction of cobalt moderately weakens the adsorption strength of nickel for carboxyl groups through electronic structure modulation, so that the catalyst preferentially adsorbs and activates benzene rings rather than carboxyl groups, thereby achieving high selectivity for directional hydrogenation of benzene rings.

[0043] Fourth, the continuous and dense nitrogen-doped carbon shell acts as a physical barrier, physically isolating the internal metal nanoparticles from the liquid-phase acidic reaction system, blocking the direct migration path of H⁺ to the metal surface, and inhibiting the acid etching and dissolution of the active metal; at the same time, the microporous structure of the carbon shell allows H2 molecules and organic substrate molecules to freely enter and exit, enabling the hydrogenation reaction to proceed normally.

[0044] This invention relies on the synergistic effects of a sealed carbon shell for acid isolation, nitrogen doping to regulate adsorption, and hollow confinement to prevent sintering. It achieves a stable PTA conversion rate of over 95% and a CHDA selectivity of over 95%, which is superior to that of precious metal systems. The catalyst shows no significant activity decay after 10 cycles, with extremely low metal dissolution and no obvious particle agglomeration. Moreover, the reaction conditions are mild, pure water can be used as a solvent, and no precious metals are required. It comprehensively surpasses existing technologies in terms of activity, selectivity, stability, production cost, and greenness, solving multiple pain points in the industry and possessing outstanding novelty, creativity, and industrial practical value. Attached Figure Description

[0045] Figure 1 This is a scanning electron microscope (SEM) image of the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst NiCo-NC-600 prepared in Example 1.

[0046] Figure 2 This is a transmission electron microscope (TEM) image of the hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst NiCo-NC-600 prepared in Example 1.

[0047] Figure 3 This is a high-resolution transmission electron microscope (HRTEM) image of the hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst NiCo-NC-600 prepared in Example 1. Detailed Implementation

[0048] The following will clearly describe the concept and technical effects of the present invention with reference to embodiments, so as to fully understand the purpose and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0049] A method for preparing 1,4-cyclohexanedicarboxylic acid by hydrogenation of terephthalic acid includes the following steps: adding a nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst with a hollow structure, terephthalic acid, and a solvent into a high-pressure reactor; replacing the air in the reactor with hydrogen and then filling it with hydrogen to a pressure of 1-6 MPa; heating to 100-200°C; reacting under stirring for 1-10 h; and after the reaction is completed, separating the solid and liquid components, washing, and drying to obtain 1,4-cyclohexanedicarboxylic acid.

[0050] The nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst with a hollow structure has a hollow spherical structure, including a carbon shell and nickel-cobalt metal nanoparticles supported on the inner and / or outer surfaces of the carbon shell; the thickness of the carbon shell is 5-30 nm, the specific surface area of ​​the catalyst is 200-800 m² / g, and the particle size of the nickel-cobalt metal nanoparticles is 5-20 nm.

[0051] The mass ratio of the catalyst to terephthalic acid is 1:1 to 1:10.

[0052] The solvent is any one or more of water, methanol, ethanol, isopropanol, tetrahydrofuran, or 1,4-dioxane, and the amount of the solvent used is 2 to 20 mL per millimole of terephthalic acid.

[0053] The catalyst is prepared by a method comprising the following steps: dispersing a hard template in a solvent, adding nickel salt, cobalt salt, carbon source and nitrogen source, and stirring to obtain a mixed solution; stirring and evaporating the obtained mixed solution at 40-80°C to obtain a catalyst precursor; heating the obtained precursor to 600-900°C at a heating rate of 1-10°C / min under a nitrogen or argon atmosphere, and isothermal pyrolyzing for 1-4 h to obtain a pyrolysis product; etching the obtained pyrolysis product with an alkaline solution to remove the hard template, and then washing and drying to obtain the catalyst.

[0054] The rigid template is any one of solid SiO2 microspheres, mesoporous SiO2, or SiO2 aerogel.

[0055] The nickel salt is any one of nickel nitrate, nickel chloride, or nickel acetate; the cobalt salt is any one of cobalt nitrate, cobalt chloride, or cobalt acetate.

[0056] The carbon source is any one of glucose, sucrose, furfuryl alcohol, or phenolic resin; the nitrogen source is any one of dicyandiamide, melamine, or urea.

[0057] The mass ratio of the nitrogen source to the carbon source is 1:1 to 1:10.

[0058] The total mass ratio of the nickel salt and cobalt salt to the carbon source is 1:5 to 1:15; the total mass ratio of the nickel salt and cobalt salt to the nitrogen source is 1:2 to 1:10.

[0059] Unless otherwise specified, "room temperature" in this invention means 25°C ± 5°C.

[0060] Unless otherwise specified, the raw materials such as elements or compounds used in the embodiments of this invention can be obtained through conventional commercial channels.

[0061] Example 1

[0062] Catalyst preparation:

[0063] 1. Solid SiO2 microspheres with a particle size of 500 nm were dispersed in deionized water, and nickel nitrate, cobalt nitrate, glucose and melamine were added. The molar ratio of nickel to cobalt was 1:1, the mass ratio of carbon source (glucose) to nitrogen source (melamine) was 1:1, and the total mass ratio of nickel salt and cobalt salt to carbon source was 1:15. The mixture was stirred for 1 h to obtain a mixed solution.

[0064] 2. The above mixed solution was rotary evaporated under reduced pressure at 40°C until the solvent was completely evaporated to obtain the catalyst precursor.

[0065] 3. The precursor was heated to 600°C under a nitrogen atmosphere at a heating rate of 1°C / min and pyrolyzed at a constant temperature for 1 hour to obtain the pyrolysis product SiO2@NiCo-NC-600.

[0066] 4. The pyrolysis product is etched with a 1 mol / L sodium hydroxide solution to remove the SiO2 hard template. After washing with deionized water until neutral and drying, the nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst NiCo-NC-600 with a hollow structure is obtained.

[0067] Catalyst Characterization: Figure 1 shows a scanning electron microscope (SEM) image of NiCo-NC-600, revealing that the catalyst is mainly composed of near-spherical particles, exhibiting a clear agglomeration and stacking state, forming three-dimensional loose microsphere clusters. Figure 2 shows a transmission electron microscope (TEM) image of NiCo-NC-600, further revealing its internal structure: the image shows a clear contrast of "bright center and dark edge," strongly proving that the catalyst has a hollow spherical structure. The electron beam can penetrate the central void region, resulting in high internal light transmittance, while the outer shell region has a higher electron density and appears dark. This hollow structure not only provides a large specific surface area but also is extremely beneficial for molecular diffusion and mass transfer in the catalytic reaction. Figure 3 shows a high-resolution TEM image of NiCo-NC-600, capturing the material's sharp lattice fringes. The fringes are regularly arranged and continuous, indicating that the catalyst's main body region has excellent crystallinity. The carbon shell thickness is 22 nm, the specific surface area is 330 m² / g, and the nickel-cobalt metal nanoparticle size is 16 nm.

[0068] Hydrogenation reaction of terephthalic acid:

[0069] 1. The above-mentioned NiCo-NC-600 catalyst, terephthalic acid, methanol and tetrahydrofuran mixed solvent were added to a high-pressure reactor. The mass ratio of catalyst to terephthalic acid was 1:1, the mass ratio of methanol to tetrahydrofuran was 1:1, and the concentration of terephthalic acid was 0.5 mmol / mL.

[0070] 2. After replacing the air in the reactor with hydrogen, fill the reactor with hydrogen to a pressure of 1.0 MPa, heat to 200°C, and react for 1 h with stirring.

[0071] 3. After the reaction is complete, solid-liquid separation is performed to obtain 1,4-cyclohexanedicarboxylic acid.

[0072] High performance liquid chromatography analysis showed that the conversion rate of terephthalic acid was 97.8% and the selectivity of 1,4-cyclohexanedicarboxylic acid was 97.1%.

[0073] Catalyst recycling experiment: The NiCo-NC-600 catalyst recovered after the above reaction was washed with ethanol, dried, and then reused for the hydrogenation reaction of terephthalic acid under the same conditions. After 5 cycles, the conversion rate of benzoic acid was 97.2%, and the selectivity of cyclohexanecarboxylic acid was 96.4%, indicating that the catalyst has good stability.

[0074] Example 2

[0075] Catalyst preparation:

[0076] 1. Disperse 100 nm mesoporous SiO2 microspheres in deionized water, add nickel acetate, cobalt acetate, furfuryl alcohol and urea, wherein the molar ratio of nickel to cobalt is 10:1, the mass ratio of carbon source (furfuryl alcohol) to nitrogen source (urea) is 10:1, and the total mass ratio of nickel salt and cobalt salt to carbon source is 1:5. Stir for 1 h to obtain a mixed solution.

[0077] 2. The above mixed solution was rotary evaporated under reduced pressure at 80°C until the solvent was completely evaporated to obtain the catalyst precursor.

[0078] 3. The precursor was heated to 900°C under a nitrogen atmosphere at a heating rate of 10°C / min and pyrolyzed at a constant temperature for 4 hours to obtain the pyrolysis product SiO2@NiCo-NC-900.

[0079] 4. The pyrolysis product is etched with a 4 mol / L potassium hydroxide solution to remove the SiO2 hard template. After washing with deionized water until neutral and drying, the nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst NiCo-NC-900 with a hollow structure is obtained.

[0080] Catalyst characterization: carbon shell thickness 7 nm, specific surface area 200 m² / g, nickel-cobalt metal nanoparticle size 5 nm.

[0081] Hydrogenation reaction of terephthalic acid:

[0082] 1. Add the above NiCo-NC-900 catalyst, terephthalic acid, and ethanol to a high-pressure reactor. The mass ratio of catalyst to terephthalic acid is 1:10, and the concentration of terephthalic acid is 0.05 mmol / mL.

[0083] 2. After replacing the air in the reactor with hydrogen, fill the reactor with hydrogen to a pressure of 6.0 MPa, heat to 100°C, and react for 1 h with stirring.

[0084] 3. After the reaction is complete, solid-liquid separation is performed to obtain 1,4-cyclohexanedicarboxylic acid.

[0085] High performance liquid chromatography analysis showed that the conversion rate of terephthalic acid was 98.7% and the selectivity of 1,4-cyclohexanedicarboxylic acid was 98.1%.

[0086] Catalyst recycling experiment: The NiCo-NC-900 catalyst recovered after the above reaction was washed with ethanol, dried, and then reused for the hydrogenation reaction of terephthalic acid under the same conditions. After 5 cycles, the conversion rate of benzoic acid was 97.4%, and the selectivity of cyclohexanecarboxylic acid was 97.5%, indicating that the catalyst has good stability.

[0087] Example 3

[0088] Catalyst preparation:

[0089] 1. Disperse SiO2 aerogel in deionized water, add nickel nitrate, cobalt acetate, phenolic resin and dicyandiamide, wherein the molar ratio of nickel to cobalt is 5:1, the mass ratio of carbon source (phenolic resin) to nitrogen source (dicyandiamide) is 5:1, and the total mass ratio of nickel salt and cobalt salt to carbon source is 1:10. Stir for 2 h to obtain a mixed solution.

[0090] 2. The above mixed solution was rotary evaporated under reduced pressure at 60°C until the solvent was completely evaporated to obtain the catalyst precursor.

[0091] 3. The precursor was heated to 700°C under a nitrogen atmosphere at a heating rate of 5°C / min and pyrolyzed at a constant temperature for 2 hours to obtain the pyrolysis product SiO2@NiCo-NC-700.

[0092] 4. The pyrolysis product was etched with a 2 mol / L potassium hydroxide solution to remove the SiO2 hard template. After washing with deionized water until neutral and drying, the nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst NiCo-NC-700 with a hollow structure was obtained.

[0093] Catalyst characterization: carbon shell thickness 30 nm, specific surface area 800 m² / g, nickel-cobalt metal nanoparticle size 20 nm.

[0094] Hydrogenation reaction of terephthalic acid:

[0095] 1. The above-mentioned NiCo-NC-700 catalyst, terephthalic acid, and 1,4-dioxane were added to a high-pressure reactor. The mass ratio of the catalyst to terephthalic acid was 1:5, and the concentration of terephthalic acid was 0.25 mmol / mL.

[0096] 2. After replacing the air in the reactor with hydrogen, fill the reactor with hydrogen to a pressure of 5.0 MPa, heat to 150°C, and react for 5 hours with stirring.

[0097] 3. After the reaction is complete, solid-liquid separation is performed to obtain 1,4-cyclohexanedicarboxylic acid.

[0098] High performance liquid chromatography analysis showed that the conversion rate of terephthalic acid was 97.7% and the selectivity of 1,4-cyclohexanedicarboxylic acid was 98.3%.

[0099] Catalyst recycling experiment: The NiCo-NC-700 catalyst recovered after the above reaction was washed with ethanol, dried, and then reused for the hydrogenation reaction of terephthalic acid under the same conditions. After 5 cycles, the conversion rate of benzoic acid was 97.1%, and the selectivity of cyclohexanecarboxylic acid was 97.7%, indicating that the catalyst has good stability.

[0100] Example 4

[0101] Catalyst preparation:

[0102] 1. Solid SiO2 microspheres with a particle size of 300 nm were dispersed in deionized water, and nickel chloride, cobalt chloride, sucrose and melamine were added. The molar ratio of nickel to cobalt was 2:1, the mass ratio of carbon source (sucrose) to nitrogen source (melamine) was 8:1, and the total mass ratio of nickel salt and cobalt salt to carbon source was 1:10. The mixture was stirred for 2 h to obtain a mixed solution.

[0103] 2. The above mixed solution was rotary evaporated under reduced pressure at 50°C until the solvent was completely evaporated to obtain the catalyst precursor.

[0104] 3. The precursor was heated to 800°C under a nitrogen atmosphere at a heating rate of 7°C / min and pyrolyzed at a constant temperature for 3 hours to obtain the pyrolysis product SiO2@NiCo-NC-800.

[0105] 4. The pyrolysis product is etched with a 3 mol / L sodium hydroxide solution to remove the SiO2 hard template. After washing with deionized water until neutral and drying, the nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst NiCo-NC-800 with a hollow structure is obtained.

[0106] Catalyst characterization: carbon shell thickness 14 nm, specific surface area 410 m² / g, nickel-cobalt metal nanoparticle size 11 nm.

[0107] Hydrogenation reaction of terephthalic acid:

[0108] 1. The above-mentioned NiCo-NC-800 catalyst, terephthalic acid, and isopropanol were added to a high-pressure reactor. The mass ratio of the catalyst to terephthalic acid was 1:8, and the concentration of terephthalic acid was 0.3 mmol / mL.

[0109] 2. After replacing the air in the reactor with hydrogen, fill the reactor with hydrogen to a pressure of 3.0 MPa, heat to 170°C, and react for 6 hours with stirring.

[0110] 3. After the reaction is complete, solid-liquid separation is performed to obtain 1,4-cyclohexanedicarboxylic acid.

[0111] High performance liquid chromatography analysis showed that the conversion rate of terephthalic acid was 99.1% and the selectivity of 1,4-cyclohexanedicarboxylic acid was 98.8%.

[0112] Catalyst recycling experiment: The NiCo-NC-800 catalyst recovered after the above reaction was washed with ethanol, dried, and then reused for the hydrogenation reaction of terephthalic acid under the same conditions. After 5 cycles, the conversion rate of benzoic acid was 98.5%, and the selectivity of cyclohexanecarboxylic acid was 98.1%, indicating that the catalyst has good stability.

[0113] Example 5

[0114] Catalyst preparation:

[0115] 1. Solid SiO2 microspheres with a particle size of 200 nm were dispersed in deionized water, and nickel nitrate, cobalt nitrate, glucose and dicyandiamide were added. The molar ratio of nickel to cobalt was 1:5, the mass ratio of carbon source (glucose) to nitrogen source (dicyandiamide) was 4:1, and the total mass ratio of nickel salt and cobalt salt to carbon source was 1:8. The mixture was stirred for 3 h to obtain a mixed solution.

[0116] 2. The above mixed solution was rotary evaporated under reduced pressure at 550°C until the solvent was completely evaporated to obtain the catalyst precursor.

[0117] 3. The precursor was heated to 750°C under a nitrogen atmosphere at a heating rate of 3°C / min and pyrolyzed at a constant temperature for 3 hours to obtain the pyrolysis product SiO2@NiCo-NC-750.

[0118] 4. The pyrolysis product is etched with a 2.5 mol / L sodium hydroxide solution to remove the SiO2 hard template. After washing with deionized water until neutral and drying, the nitrogen-doped carbon-coated nickel-cobalt bimetallic catalyst NiCo-NC-750 with a hollow structure is obtained.

[0119] Catalyst characterization: carbon shell thickness 12 nm, specific surface area 460 m² / g, nickel-cobalt metal nanoparticle size 8 nm.

[0120] Hydrogenation reaction of terephthalic acid:

[0121] 1. Add the above NiCo-NC-750 catalyst, terephthalic acid, and water to a high-pressure reactor. The mass ratio of catalyst to terephthalic acid is 1:8, and the concentration of terephthalic acid is 0.4 mmol / mL.

[0122] 2. After replacing the air in the reactor with hydrogen, fill the reactor with hydrogen to a pressure of 3.5 MPa, heat to 140°C, and react for 3 hours with stirring.

[0123] 3. After the reaction is complete, solid-liquid separation is performed to obtain 1,4-cyclohexanedicarboxylic acid.

[0124] High performance liquid chromatography analysis showed that the conversion rate of terephthalic acid was 99.5% and the selectivity of 1,4-cyclohexanedicarboxylic acid was 99.3%.

[0125] Catalyst recycling experiment: The NiCo-NC-750 catalyst recovered after the above reaction was washed with ethanol, dried, and then reused for the hydrogenation reaction of terephthalic acid under the same conditions. After 5 cycles, the conversion rate of benzoic acid was 98.9%, and the selectivity of cyclohexanecarboxylic acid was 98.7%, indicating that the catalyst has good stability.

[0126] The technical solutions disclosed and proposed in this invention can be implemented by those skilled in the art by appropriately modifying the conditions and routes, etc. Although the methods and preparation techniques of this invention have been described through preferred embodiments, those skilled in the art can obviously modify or recombine the methods and technical routes described herein without departing from the content, spirit, and scope of this invention to achieve the final preparation technique. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the spirit, scope, and content of this invention.

Claims

1. A hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst, characterized in that, The catalyst has a hollow spherical core-shell microstructure with a hollow cavity inside and a continuous nitrogen-doped carbon shell on the outside. Nickel-cobalt bimetallic nanoparticles are uniformly embedded in the inner wall and surface of the carbon shell.

2. The method for preparing the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst of claim 1, characterized in that, Includes the following steps: 1) Disperse the hard template in a solvent, add nickel salt, cobalt salt, carbon source and nitrogen source, stir for 1-4 h to obtain a mixed solution; 2) The mixed solution is rotary evaporated under reduced pressure at 40-80°C until the solvent is completely evaporated to obtain the catalyst precursor; 3) The obtained precursor is heated to 600-900°C at a heating rate of 1-10°C / min under a nitrogen or argon atmosphere and pyrolyzed at a constant temperature for 1-4 h to obtain the pyrolysis product; 4) The obtained pyrolysis product was etched with alkaline solution to remove the hard template. After washing and drying, a hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst was obtained.

3. The preparation method of the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst as described in claim 2, characterized in that, The rigid template is any one of solid SiO2 microspheres, mesoporous SiO2, or SiO2 aerogel.

4. The preparation method of the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst as described in claim 2, characterized in that, The nickel salt is any one of nickel nitrate, nickel chloride, or nickel acetate; the cobalt salt is any one of cobalt nitrate, cobalt chloride, or cobalt acetate.

5. The preparation method of the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst as described in claim 2, characterized in that, The carbon source is any one of glucose, sucrose, furfuryl alcohol, or phenolic resin; the nitrogen source is any one of dicyandiamide, melamine, or urea; the mass ratio of nitrogen source to carbon source is 1:1 to 1:

10.

6. The preparation method of the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst as described in claim 2, characterized in that, The total mass ratio of the nickel salt and cobalt salt to the nitrogen source is 1:2 to 1:10; the total mass ratio of the nickel salt and cobalt salt to the carbon source is 1:5 to 1:

15.

7. The preparation method of the hollow nitrogen-doped carbon sphere supported bimetallic nickel-cobalt catalyst as described in claim 2, characterized in that, The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 1–4 mol / L.

8. A method for preparing 1,4-cyclohexanedicarboxylic acid by catalytic hydrogenation of terephthalic acid using the catalyst of claim 1, characterized in that, Includes the following steps: 1) Add the hollow nitrogen-doped carbon sphere-supported bimetallic nickel-cobalt catalyst, terephthalic acid, and solvent into a high-pressure reactor and seal the reactor; 2) After replacing the air in the reactor with hydrogen, fill it with hydrogen to a pressure of 1.0–6.0 MPa, heat it to 100–200°C, and react it with stirring for 1–10 h; 3) After the reaction is complete, allow the autoclave to cool naturally to room temperature, and then separate the solid and liquid phases to obtain 1,4-cyclohexanedicarboxylic acid.

9. The method for preparing 1,4-cyclohexanedicarboxylic acid by catalytic hydrogenation of terephthalic acid as described in claim 8, characterized in that, The mass ratio of catalyst to terephthalic acid is 1:1 to 1:10; the concentration of terephthalic acid is 0.05 to 0.5 mmol / mL.

10. The method for preparing 1,4-cyclohexanedicarboxylic acid by catalytic hydrogenation of terephthalic acid as described in claim 8, characterized in that, The solvent is one or more of water, methanol, ethanol, isopropanol, tetrahydrofuran, or 1,4-dioxane.